'Blended learning' as an effective teaching and learning strategy in the classroom - Batumalai, Vigneswari; Kamarudin, Nurzatulshima (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
There are so many ways in teaching and learning in our education system. The teachers in schools are slowly changing the traditional method to modern teaching such as incorporating the elements of ICT in the subjects. This is an innovative way where the students are being exposed to the outside world through the eye of technology. However, the implementation of these methods are not as easy as it seems if there are not enough support from the schools or administrative. There are so many types of blended learning strategies and the teachers can choose different types of models which are suitable for the classroom. There are so many advantages blended learning and it can help the teachers and the students in so many ways. Nevertheless, there are some disadvantages in these methods where it can hinder the effectiveness of the implementation in the classroom.